The iconography of humiliation in New Kingdom Egypt - Janzen, Mark, 1980- author. Link
1 online resource (xix, 269 pages)
Keywords: "This volume analyzes the iconography of bound foreigners on New Kingdom monuments and artifacts in order to better understand Egyptian perspectives on foreigners and their treatment of prisoners of war. Depictions of foreign captives in humiliating or torturous poses are ubiquitous in Egyptian iconography and reflect the celebratory nature of royal ideology, in this case by degrading enemies. Egyptologists have scrutinized these scenes for details regarding various military matters, but existing scholarly literature offers few studies focused on enemy captives and the sheer physical brutality of the depictions of their bindings. Janzen examines the bound foreigner motif in New Kingdom sources, demonstrating that these prisoners of war played vital roles in Egyptian ideology and religion. Their depictions in bizarre or torturous poses served to reinforce ideological underpinnings of pharaoh's right to rule, perpetually ritualizing their defeat and/or punishment through the presence of this iconography on ceremonial objects used primarily by the king and on temple walls and monuments. The subjugation of foreigners also constituted an important economic function, as incorporating prisoners of war into the Egyptian workforce was crucial for economic prosperity and growth in New Kingdom Egypt. The volume also explores cross-cultural and anthropological parallels, placing Egyptian treatment of foreign prisoners in its ancient context. The book provides a fascinating study of the subject suitable for scholars and students of Egyptology and ancient history, particularly that of New Kingdom Egypt, as well as those working on power, warfare, and violence in the ancient world more broadly"--